Development and evaluation of a physical activity intervention for older adults - Jancey, Jonine Maree (Curtin University, 2007)
The present knowledge of factors associated with older adults’ physical activity behaviour is limited. Therefore, this study trialled an innovative physical activity program for older adults, investigating effective recruitment and retention strategies, and exploring the adults’ perceptions of physical activity. A total of 573 subjects were recruited into the quasi-randomised controlled trial, located in 30 intervention and 30 control neighbourhoods in the Perth metropolitan area. The initial response rate was 74% (260/352) in the intervention group and 82% (313/382) in the control group. Self-reported questionnaires administered at three time points (baseline, 3-months, 6-months) measured physical activity levels, personal and demographic information, including perception of financial struggle, proximity to friends, and other psychosocial data. Descriptive statistics, repeated measure analysis of variance, logistic regression and generalised estimating equations were used in the analysis. Qualitative data on the participants’ perceptions of physical activity were collected through one-on-one interviews (n=16). The results showed that: 1. This cost-effective recruitment procedure facilitated the selection of a reasonably representative sample of 65 to 74 year olds from the Perth metropolitan area. Names of 7378 older adults were obtained from the Federal Electoral Roll, then 6401 potential subjects were matched to telephone numbers and phoned with subjects meeting the screening criteria invited to join the program (n = 4209). From this sample, 573 subjects were recruited. More females (63%) than males (37%) were recruited.The study attracted a greater proportion of ‘obese’ older adults (27%) relative to state averages. 2. Over the intervention period there was a significant increase in participants’ total physical activity of 2.25 hours per week (p >.001). The General Estimating Equation analysis confirmed significant increase in physical activity from baseline to midpoint (p=.002) and to post intervention (p=.0031). Perceptions of financial struggle (p=.020) were positively correlated with physical activity time spent by participants, whereas having friends or acquaintances living nearby (p=.037) had a significant negative correlation with physical activity time. 3. At the end of the intervention, 32% of the intervention group and 25% of the control group had dropped out, resulting in an overall drop out rate of 28%. Most of the attrition occurred in the first 3 months (77%). Characteristics of individuals lost to attrition (n=86, 35%) were compared with program completers (n=162, 65%). Logistic regression analysis showed that those lost to attrition came from areas of lower socio-economic status, were overweight, were less physically active, and had a lower walking self-efficacy score and a higher loneliness score. The results suggest that to improve retention and to avoid potential bias, early assessment of these characteristics should be undertaken to identify individuals at risk of attrition. 4. Based on the finding of this research, future intervention studies should consider: the role of tertiary students as a skilled resource; the use of volunteers to contain costs; the importance of a tailored program; the appropriateness of walking as a form of physical activity for this age group; the enjoyment associated with a walking group; and the usefulness of social support.This practical program is potentially effective and sustainable for mobilizing physically inactive older people. 5. Qualitative research highlighted the need for older adults to receive more specific information on: the benefits of physical activity; the role of pain management in physical activity; and the concept that involvement in physical activity in younger years leads to involvement when older. The older adults also expressed a desire to engage in less age appropriate activities. These results suggest that the intervention was successful in recruiting older adults into and retaining them in the intervention, documenting a need for early identification of individuals at risk of attrition. The program significantly increased the participants’ weekly mean time for physical activity and identified factors that affect their commitment to physical activity programs. This program was practical and could be used as a model for physical activity programs aimed at older adults.